THE EFFECTS OF EARNINGS MANAGEMENT ON ACCOUNTING CONSERVATISM MODERATED BY CORPORATE GOVERNANCE MECHANISM (STUDY OF MANUFACTURING COMPANIES LISTEDON INDONESIA STOCK EXCHANGEIN 2008 – 2010) - AMMAR AL ASYARI; RIDA PRIHATNI; ETTY GURENDRAWATI (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
ABSTRACT This study aimsto examine earnings management by companies manufacturing in Indonesia affect the choice of managers to implement aconservative accounting policy. With corporate governance mechanisms in influencing the relationship of Earning Management on Accounting Conservatism. Methods of analysis using multiple linear regression analysis with one independent variable, one dependent variable and two variables moderation. Corporate governance mechanismuses two characteristics as moderating variables, managerial ownership and board of commissioners. Size using the accrua lconservatism, according to those used by Givolyand Hayn (2002) and discretionary accruals as aproxy for earnings management is computed using the Modified Jones Model (Dechow etal., 1995). By using the purposive sampling method, the sample in this research consists of 23 manufacturing companies that listed on Indonesia Stock Exchange in 2008 – 2010. This research use secondary data which is collected from the firm’s annual report and financial statements. The result of this research shows that simultaneously, earning management, managerial ownership, and board of commissioners influence accounting conservatism. Partially, only earning management that significantly influences accounting conservatism. While managerial ownership and board of commissioners do not significantly influence the relationship of Earning Management on Accounting Conservatism. Keywords: corporate governance, accounting conservatism, earning management, managerial ownership, board of commissioners.